ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2015) - Danang Tri Atmojo; Darsono Darsono (Diponegoro Journal of Accounting, 2017)
The purpose of this research is to analyze the factors that affect audit report lag of financial reports to the companies listed on the Indonesia Stock Exchange. The examined factors of this research are board independence, audit committee, ownership consentration, size company, complexity of the company’s operation, auditor type and auditor opinion as the independent variable, while the audit report lag as the dependent variable.The populations in this study are all companies listed in the Indonesia Stock Exchange in the period 2013-2015. The sample consists of 1540 companies listed in the Indonesia Stock Exchange (IDX) and submitted financial reports to Bapepam in the period 2013-2015. The data that was used in this research was secondary data and selected by using purposive sampling method. Model analysis using multiple linear regression analysis. Using the F-test to determine the effect of simultaneous between company characteristics and capital structure. Using t-test to examine the partial correlation of each independent variable on audit report lag.Based on analytical results shows that variable audit committee, ownership concentration, size company and auditor opinion have significant influence toward audit report lag, while variable board independence, complexity of the company’s operation and auditor type doesn’t have significant influence toward audit report lag.